Zig-zag surface step migration and structure modulation in metallic nanowires - Li, Xiyao (2024)
Nanoscale metals frequently exhibit novel mechanical properties or physiochemical performances, due to the growing influence of surfaces. Here, we uncover a unique surface-mediated deformation behavior of Au nanowires by conducting in situ transmission electron microscope tensile testing. A zig-zag migration of surface steps via the transverse slips on alternate (111) and (001) planes is revealed in [112]-oriented Au nanowire, which contributes to unexpected uniform deformation with an elongation of 108.9%. Further, we discover that the unusual (001) slip can induce an anomalous stacking structure on the nanowire surface under uniaxial tension. These findings enrich our understanding of surface-mediated plasticity in metallic nanomaterials.